UJI AKTIVITAS ANTIBAKTERI EKSTRAK BUAH Rivina humilis L. TERHADAP Klebsiella pneumoniae DAN Escherichia coli - mariyam mariyam (Journal of Science and Applicative Technology, 2018)
Rivina humilis L. is herbaceous bushy perennial plant found in shrubs. The fruit extract of Rivina humilis L. had experienced antibacterial activity against Klebsiella pneumoniae and Escherichia coli. The crude extract of nonpolar fraction (n-hexane) of Rivina humilis L. showed negative antibacterial activity towards Klebsiella pneumoniae and Escherichia coli whereas the methanolic extract has antibacterial activity with 12 mm of inhibition zone for Klebsiella pneumoniae and 10 mm for E.coli in 1 ppm concentration. Determination of MIC (Minimum Inhibitory Concentration) was conducted with variation of concentration (w/v) 1 ppm; 0.8 ppm; 0.6 ppm; 0.2 ppm; 0 ppm (negative control), and chloramphenicol (positive control). The result of MIC determination against Klebsiella pneumoniae showed that the width and the inhibition zone index in the minimum concentration (0.2 ppm) were 7 mm and 1.36, respectively. While towards E.coli, MIC determination exhibited positive result at 0.6 ppm with the width and the inhibition zone index were 8 mm and 1.78 respectively.